Respuesta :
Answer with explanation:
1. The given rational expression is
[tex]\rightarrow\frac{x^2+5 x+6}{x^2-9}\\\\\rightarrow\frac{x^2+5 x+6}{(x-3)(x+3)}[/tex]
The function is not defined ,when
→(x-3)(x+3)=0
→x-3≠0 ∧ x+3≠0
→x≠3, ∧ x ≠ -3
⇒Option C and D
→x≠−3
→x≠3
2.
[tex]\rightarrow\frac{4 x}{x-3}+\frac{2}{x^2-9}=\frac{1}{x+3}\\\\\rightarrow\frac{4 x}{x-3}+\frac{2}{(x-3)(x+3)}=\frac{1}{x+3}\\\\\rightarrow\frac{4 x(x+3)+2}{(x-3)(x+3)}=\frac{1}{x+3}\\\\\rightarrow4 x(x+3)+2=\frac{(x-3)(x+3)}{x+3}\\\\\rightarrow4x^2+12 x+2=x-3\\\\\rightarrow4x^2+11x+5=0\\\\ \text{Using Discriminant method for a quadratic equation}\\\\ax^2+bx +c=0\\\\x=\frac{-b\pm\sqrt{D}}{2 a}\\\\D=b^2-4 ac\\\\x=\frac{-11\pm\sqrt{121-80}}{2 \times 4}\\\\x=\frac{-11\pm\sqrt{41}}{8}[/tex]
None of the option
3.
[tex]\rightarrow \frac{1}{x}+\frac{1}{x-3}=\frac{x-2}{x-3}\\\\\rightarrow\frac{x-3+x}{x(x-3)}=\frac{x-2}{x-3}\\\\\rightarrow2x-3=\frac{x(x-3)(x-2)}{x-3}\\\\\rightarrow 2 x-3=x^2-2 x\\\\\rightarrow x^2-4x+3=0\\\\\rightarrow (x-1)(x-3)=0\\\\x=1,3[/tex]
For, x=3 , the equation is not defined.
So, there is single solution which is , x=1.
Option B:→ There is only one solution: x = 1.
The solution x = 3 is an extraneous solution.
4.
[tex]\rightarrow \sqrt{3}x+1-x+3=0\\\\\rightarrow \sqrt{3}x -x=-4\\\\\rightarrow x(\sqrt{3}-1)=-4\\\\\rightarrow x=\frac{-4}{\sqrt{3}-1}\\\\\rightarrow x=\frac{-4\times(\sqrt{3}+1)}{(\sqrt{3}-1)(\sqrt{3}+1)}\\\\x=\frac{-4\times(\sqrt{3}+1)}{2}\\\\x=-2(\sqrt{3}+1)[/tex]
None of the option
1) Options c) and d) are correct.
2) None of the options are correct.
3) Option B) is correct.
4) None of the options are correct.
Step-by-step explanation:
1) Given : [tex]4x^2+12x+2=x-3[/tex]
Expression -- [tex]\dfrac{x^2+5x+6}{x^2-9}[/tex]
Solution :
[tex]\dfrac{x^2+5x+6}{x^2-9}=\dfrac{x^2+3x+2x+6}{(x+3)(x-3)}[/tex]
[tex]\dfrac{x^2+5x+6}{x^2-9}=\dfrac{(x+3)(x+2)}{(x+3)(x-3)}[/tex]
Therefore, [tex]\rm x\neq 3 \; and\;x\neq -3[/tex] ,option c) and d) is correct.
2) Given :
Expression - [tex]\dfrac{4x}{x-3}+\dfrac{2}{x^2-9}=\dfrac{1}{x+3}[/tex]
Solution :
[tex]\dfrac{4x}{(x-3)}+\dfrac{2}{(x+3)(x-3)}=\dfrac{1}{(x+3)}[/tex]
[tex]\dfrac{4x(x+3)+2}{(x-3)(x+3)}=\dfrac{1}{(x+3)}[/tex]
[tex]4x^2+12x+2=x-3[/tex]
[tex]4x^2+11x+5=0[/tex]
[tex]x=\dfrac{-11\pm\sqrt{121-80} }{8}[/tex]
[tex]x = \dfrac{-11\pm\sqrt{41} }{8}[/tex]
None of the options are correct.
3) Given :
Expression - [tex]\dfrac{1}{x}+\dfrac{1}{x-3}=\dfrac{x-2}{x-3}[/tex] ----- (1)
Solution :
[tex]\dfrac{x-3+x}{(x)(x-3)}=\dfrac{x-2}{x-3}[/tex]
[tex]2x-3=x(x-2)[/tex]
[tex]x^2-4x+3=0[/tex]
[tex]x^2-3x-x+3=0[/tex]
[tex](x-3)(x-1)=0[/tex]
At x = 3 equation (1) is not define. Therefore, the correct answer is option
B) There is only one solution: x = 1. The solution x = 3 is an extraneous solution.
4) Given :
Exprression - [tex](\sqrt{3}x +1)-x+3=0[/tex]
Solution :
[tex]x(\sqrt{3}-1 )=-4[/tex]
[tex]x=\dfrac{-4}{\sqrt{3}-1 }[/tex]
None of the options are correct.
For more information, refer to the link given below
https://brainly.com/question/11536910?referrer=searchResults